2010
DOI: 10.1128/mcb.00444-09
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Histone Demethylase JMJD1A by Hypoxia-Inducible Factor 1α Enhances Hypoxic Gene Expression and Tumor Growth

Abstract: The hypoxia-inducible transcription factors (HIFs) directly and indirectly mediate cellular adaptation to reduced oxygen tensions. Recent studies have shown that the histone demethylase genes JMJD1A, JMJD2B, and JARID1B are HIF targets, suggesting that HIFs indirectly influence gene expression at the level of histone methylation under hypoxia. In this study, we identify a subset of hypoxia-inducible genes that are dependent on JMJD1A in both renal cell and colon carcinoma cell lines. JMJD1A regulates the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
319
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 314 publications
(334 citation statements)
references
References 59 publications
12
319
1
1
Order By: Relevance
“…However, we did find a correlation of CDCP1 cell surface expression with patient outcome: 50% of patients positive for CDCP1 on the membrane die by 90 mo of the followup; >75% of patients with negative or cytoplasmic CDCP1 are alive at the end of the followup, which is 119 mo. Thus, our data suggest that CDCP1 expression might play a crucial role in (12). We found that CDCP1 mRNA was increased with VHL loss (RCC4 vs. RCC-VHL cells), and CDCP1 expression was induced at least threefold upon hypoxic exposure of RCC4-VHL (Fig.…”
mentioning
confidence: 50%
“…However, we did find a correlation of CDCP1 cell surface expression with patient outcome: 50% of patients positive for CDCP1 on the membrane die by 90 mo of the followup; >75% of patients with negative or cytoplasmic CDCP1 are alive at the end of the followup, which is 119 mo. Thus, our data suggest that CDCP1 expression might play a crucial role in (12). We found that CDCP1 mRNA was increased with VHL loss (RCC4 vs. RCC-VHL cells), and CDCP1 expression was induced at least threefold upon hypoxic exposure of RCC4-VHL (Fig.…”
mentioning
confidence: 50%
“…In parallel, ChIP-chip analysis was used to identify genes bound by HIF-1 or HIF-2 within promoter regions of RCC4 cells. The screen identified several known HIF target genes, including vascular endothelial growth factor (VEGF), providing validity for our ChIP-chip analysis (15). We were particularly interested in identifying HIF targets that could be molecular targets for ccRCC therapy, including secreted factors, receptors, or kinases.…”
Section: Resultsmentioning
confidence: 99%
“…To identify novel molecular targets involved in ccRCC tumor progression and metastasis, we performed a directed screen by combining high-throughput chromatin immunoprecipitation (ChIP-chip) with gene expression analysis to identify functionally relevant HIF target genes (15) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…13,34 Recent studies have shown that JMJD1A is the target of hypoxia-inducible transcription factors and under hypoxia JMJD1A increases a subset of hypoxia-inducible genes enhancing tumor growth. 35 …”
Section: Jmjd1/kdm3mentioning
confidence: 99%